Latihan Massed Practice dan Distribute Practice untuk Akurasi Tendangan ke Gawang - Saifudin, Mohamad; -, Soegiyanto; -, Sugiharto (Media Ilmu Keolahragaan Indonesia, 2013)
The purpose of this research was to determine the effect training of massed practice and distribute practice to the accuracy of shots on goal and a better workout between massed practice and distribute practice. This research uses pre test and post-test group design the experimental method or pattern matching by subject MS. The population of the research is Jatidiri Futsal players Semarang, 14 samples. Research sampling technique using total sampling technique. The data were then analyzed using paired t-test pattern with a significance level of 5%. Based on data analysis, showed the following results 1) mean test accuracy shots on goal massed practice group training Pree test 47.5 post-test 90. 2) mean test accuracy shots on goal to distribute practice group training Pree test 51.2 post-test 80. different test results using the t-test formula is 2.645 greater than 2.447 t-table so that significant results. The conclusion of this research is 1) massed practice and distribute practice training influential to the increase in accuracy shots on goal. 2) Massed practice training is more effective against shots on goal accuracy than distribute practice training. Suggestion is to improve the accuracy of shots massed practice can be used by trainers besides using the training by turns shooting at goal.